Influence of carbon dioxide stunning procedure on quality of turkey meat. Issue 4 (4th July 2017) - Mauri, S.; Guijarro, A.; Avilés, C.; Peña, F.
ABSTRACT: 1. The objective of this study was to evaluate the effect of sex and gas stunning on quality attributes of turkey breast meat. 2. One hundred B.U.T. Premium turkeys (50 males and 50 females) were divided into four groups of 25 animals and subjected to one of two CO2 stunning procedures: G1 stepwise (step 1: 30% CO2, 15 s; step 2: 55% CO2, 40 s; step 3: 70% CO2, 45 s) or G2 fixed concentration (80% CO2, 100 s). The pH and meat colour at 20 min post-mortem, and pH, colour (L*, a*, b*), water holding capacity (WHC), drip loss (DL), cooking loss (CL) and Warner–Bratzler shear force (WBSF) in breast samples at 24 h and 7 d post-mortem were assessed. 3. There were significant differences between stunning groups for pH, meat colour and CL, whereas no significant differences were found for DL and WBSF. Sex had a significant effect on pH and b* and ageing of meat affected pH, colour coordinates, DL and WBSF. 4. It was concluded that the G2 treatment affected negatively the pH value and colour coordinates. However, G2 stunning affected positively the WHC parameters. Female turkeys had better results than males for pH, and the colour of female turkey breast meat was less yellow than male breast meat.